2008
DOI: 10.1002/pssb.200844047
|View full text |Cite
|
Sign up to set email alerts
|

Local microstructure of amorphous Al2O3

Abstract: We present a microstructure study of different amorphous states of Al2O3, which are constructed by compressing the original glass to different pressure and then decompressing. The local microstructure of these states is analyzed through the coordination number, bond‐angle statistics, the characteristics of voids and void aggregations. The simulation results indicate the possibility of amorphous–amorphous phase transition from low‐density to high‐density Al2O3 with gradual variation in density and other structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Our calculated RDFs for a -Al 2 O 3 and a -AlF 3 are shown in Figure and for a -Al 2 O 3 , we compare with experimental observations. This comparison suggests that, for a -Al 2 O 3 , the calculated position and shape of the peaks agree very well with observations . Unfortunately, to the authors’ best knowledge, there are no a -AlF 3 RDF observations available to compare with our calculated results.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Our calculated RDFs for a -Al 2 O 3 and a -AlF 3 are shown in Figure and for a -Al 2 O 3 , we compare with experimental observations. This comparison suggests that, for a -Al 2 O 3 , the calculated position and shape of the peaks agree very well with observations . Unfortunately, to the authors’ best knowledge, there are no a -AlF 3 RDF observations available to compare with our calculated results.…”
Section: Resultssupporting
confidence: 83%
“…This comparison suggests that, for a-Al 2 O 3 , the calculated position and shape of the peaks agree very well with observations. 19 Unfortunately, to the authors' best knowledge, there are no a-AlF 3 RDF observations available to compare with our calculated results. From the peak position in the calculated RDF for a-AlF 3 , the average Al−F bond is about 1.86 Å, which is higher than the corresponding calculated Al−F bond in crystalline phase 1.80 Å.…”
Section: ■ Resultsmentioning
confidence: 87%
“…Miguel et al [21] found that more than 50% of Al atoms are tetrahedral coordinated at four different temperatures. According to Hoang et al [22] and Hung et al [23], they showed the clear evidence of structural transition in liquid Al2O3 from a tetrahedral to an octahedral network. The voids created a very large hole with a volume five times bigger than that of the aluminum atom.…”
Section: Introductionmentioning
confidence: 99%